2021
DOI: 10.1111/os.12923
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA circ‐IQGAP1 Knockdown Alleviates Interleukin‐1β‐Induced Osteoarthritis Progression via Targeting miR‐671‐5p/TCF4

Abstract: Objective To explore the function of circular RNA IQ motif‐containing GTPase‐activating protein 1 (circ‐IQGAP1) in interleukin (IL)‐1β‐induced osteoarthritis (OA) model and to explore whether circ‐IQGAP1 can modulate microRNA‐671‐5p (miR‐671‐5p) and transcription factor 4 (TCF4) to regulate chondrocyte apoptosis, inflammatory injury, and extracellular matrix degradation. Methods The cartilage tissues were collected from 32 OA patients or normal subjects. Human chondrocyte CHON‐001 cells were challenged via dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…For instance, circ-SERPINE2 is reported to restrain OA progression by regulating miR-1271 and ETS-associated molecules [25]. Circ-IQGAP1 silencing is reported to attenuate IL-1β-mediated OA development by targeting miR-671-5p/TCF4 axis [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, circ-SERPINE2 is reported to restrain OA progression by regulating miR-1271 and ETS-associated molecules [25]. Circ-IQGAP1 silencing is reported to attenuate IL-1β-mediated OA development by targeting miR-671-5p/TCF4 axis [26].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al found that miR-671 attenuates OA development in vitro and in vivo [17]. Xi et al found that miR-671-5p is down-regulated in chondrocytes induced by IL-1β, and circ-IQGAP1 contributes to IL-1β-induced OA development by down-regulating miR-671-5p and up-regulating TCF4 [26]. Consistent with these studies, we found that miR-671-5p overexpression protected chondrocytes from IL-1β-induced injury in chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Wang et al showed that miR-203 inhibits inflammation to alleviate myocardial ischaemia–reperfusion injury [ 37 ]. It has been reported that miR-671-5p represses cell proliferation, migration, invasion and the inflammatory response [ 38 ]. MiR-671 mimics ameliorated IL-1β-induced proliferation inhibition and apoptosis stimulation and alleviated the progression of osteoarthritis in mice [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Upstream circRNA usually acts as a miRNA sponge in cells and weakens the inhibitory effect of miR-671 on inflammation through the competitive binding of miR-671. Compared with healthy people, the expression of circ-IQGAP1 and circ_0114876 increases in cartilage tissues, while the expression of miR-671-5p decreases ( 41 ). Reducing circRNA content can reduce chondrocyte apoptosis, inflammatory cytokine secretion, and extracellular matrix degradation induced by IL-1β.…”
Section: Mir-671 In Bone-related Inflammatory Diseasesmentioning
confidence: 99%